Inhibition of Return Affects Contrast Sensitivity. Issue 7 (July 2014) - Sapir, Ayelet; Jackson, Kevin; Butler, Joe; Paul, Matthew A.; Abrams, Richard A.
Inhibition of return (IOR)—a slow response to targets at recently attended locations, is believed to play an important role in guiding behaviour. In the attention literature it has been shown that attentional capture by an exogenous cue affects contrast sensitivity so that it alters the appearance of low-contrast stimuli. Despite a significant amount of work over the last quarter century on IOR, it is not yet clear whether IOR operates in the same way. In the current study we examined the effect of IOR on contrast sensitivity—a very early, low-level perceptual process. We found in both a detection task and an orientation discrimination task that lower contrast was needed to detect the stimulus (Experiment 1) and determine its orientation (Experiment 2) at the cued location than at the uncued location, at short cue–target delays, while higher contrast was needed at long delays—reflecting IOR. These results clearly demonstrate that IOR affects contrast sensitivity in a similar way as attentional capture does and suggest that IOR increases perceived contrast of an object in the uncued location.